2006
DOI: 10.1158/0008-5472.can-06-2011
|View full text |Cite|
|
Sign up to set email alerts
|

Down-regulation of Androgen Receptor by 3,3′-Diindolylmethane Contributes to Inhibition of Cell Proliferation and Induction of Apoptosis in Both Hormone-Sensitive LNCaP and Insensitive C4-2B Prostate Cancer Cells

Abstract: Despite the initial efficacy of androgen deprivation therapy, most patients with advanced prostate cancer eventually progress to hormone-refractory prostate cancer, for which there is no curative therapy. Previous studies from our laboratory and others have shown the antiproliferative and proapoptotic effects of 3,3 ¶-diindolylmethane (DIM) in prostate cancer cells. However, the molecular mechanism of action of DIM has not been investigated in androgen receptor (AR)-positive hormoneresponsive and -nonresponsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
126
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(146 citation statements)
references
References 38 publications
(49 reference statements)
17
126
2
1
Order By: Relevance
“…Despite the fact that many studies have revealed that DIM has antitumor effects in a variety of cancer cells including prostate, breast, pancreas, and esophageal cancer cells through the NF-κB, Akt, MAPK, p53, AR, and ER pathways (5,11,28,31,34,42), no information is available regarding the functional role of the Hippo signal transduction pathway in mediating DIM-induced lethality in gastric cancer cells. We found that DIM was effective in sensitizing gastric cancer cells through activation of the Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that many studies have revealed that DIM has antitumor effects in a variety of cancer cells including prostate, breast, pancreas, and esophageal cancer cells through the NF-κB, Akt, MAPK, p53, AR, and ER pathways (5,11,28,31,34,42), no information is available regarding the functional role of the Hippo signal transduction pathway in mediating DIM-induced lethality in gastric cancer cells. We found that DIM was effective in sensitizing gastric cancer cells through activation of the Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…I3C is chemically unstable in aqueous environments and is rapidly converted to DIM, which is a major condensation product in the stomach (25)(26)(27). DIM is the predominant bioactive compound in plasma (27), and recent studies have shown that DIM has anticancer effects in both in vivo and in vitro models of various types of cancers (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). However, the biological function of 3,3'-Diindolylmethane suppresses the growth of gastric cancer cells via activation of the Hippo signaling pathway DIM, and its possible use as an antitumor agent for human gastric cancer, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Both I3C and DIM have been widely shown to exert anticancer effects in vivo (4) and in vitro (5,6). Use of an absorption enhanced formulation of DIM (27) in mice has shown a significant inhibition of C4-2B prostate tumors thereby validating efficacy in a tumor model of prostate cancer growth (28).…”
Section: Discussionmentioning
confidence: 99%
“…DIM is thought to inhibit cancer cell proliferation through several distinct yet overlapping mechanisms. By selectively binding and down-regulating AR activity, reducing AR-specific genes expression [11][12][13] and by inhibiting signaling through pro-survival regulators such as PI3K, Akt, mTOR and GSK3β, DIM inhibits cancer cell proliferation [14][15][16][17][18]. DIM also induces cancer cell death by increasing the intracellular flux of calcium ions, resulting in the induction of endoplasmic reticulum (ER) stress genes [19][20][21], and induces apoptosis through up-regulation of Fas and FasL or activation of death receptor 5 (DR5), leading to activation of caspase-dependent extrinsic apoptosis pathways [22][23][24].…”
Section: Introductionmentioning
confidence: 99%